Determination of copper in traditional coffee pot water samples by flame atomic absorption spectrometry and matrix matching calibration strategy after switchable solvent based liquid-phase microextraction - Ercan, Maral Selin Findikoglu; Ayyildiz, Merve Firat; Chormey, Dotse Selali; Bakirdere, Sezgin (SPRINGER, 2021)
Traditional copper coffee pots are widely used in these modern times and daily consumption of coffee brewed in overused/old pots increases the risk of copper ingestion. This study employed a green switchable solvent-based liquid-phase microextraction (SS-LPME) method to isolate and preconcentrate copper from water boiled in coffee pots. Copper was determined by a flame atomic absorption spectrometry (FAAS) system coupled with a slotted quartz tube (SQT). 1,5-Diphenylcarbazone was added to aqueous samples to form a complex with copper before the extraction step. Box-Behnken experimental design was applied to select optimum conditions of the extraction method that were used to validate the analytical method. The limits of quantification and detection of the optimized SS-LPME-SQT-FAAS method were determined as 9.1 and 2.7 mu g/L, respectively. Water samples boiled in traditional coffee pots were spiked at different concentrations and analyzed to ascertain the method's accuracy and applicability to real samples. Satisfactory recovery results obtained in the range of 92-107% established good accuracy, and percent relative standard deviations lower than 8.0% also proved high precision.
Keywords: Copper; FAAS; SS-LPME; SQT; Experimental design; SPECTROPHOTOMETRIC DETERMINATION; FAAS DETERMINATION; IONIC LIQUID; PRECONCENTRATION; EXTRACTION; FOOD; CHROMIUM; ALUMINUM; VANADIUM; NICKEL; Environmental Sciences & Ecology